Modelagem Born-raio em meios anisotrópicos - PINHEIRO, Brenno Carneiro (2019)
The simulation of wave propagation in sedimentary basins is essential for processing and imaging reflection seismic data. For example, design of acquisition parameters, illumination studies, validation of imaging and velocity analysis algorithms. Anisotropy in sedimentary basins is mainly associated to shales and fractured rocks, for example, carbonates. Numerical modeling of wave propagation in inhomogeneous anisotropic media, using the complete solution of the wave equation, is computationally expensive. Moreover, some of the events resulting from a complete solution are considered noise in reflection seismic, i.e., surface waves and multiples. The combination of Born approximation, ray theory and the assumption of elliptical anisotropy, for qP waves, highly improves e ciency for the computation of primary reflection and diffraction events in inhomogeneous and anisotropic media.